The Concept of Miracle in the Qur'an Form Mohammed Arkoun's Point of View - Sri Mulyati (Refleksi, 2000)
The concept of Qur'an as a miracle of Muhammad is an Islamic doctrine that has engaged Muslim thinkers for many generations, with the literature on the issue of i'jaz continuing to grow from the third/ninth century onward.